Pollution source of Cileungsi-Cikeas-Bekasi River. Issue 1 (April 2021) - Effendi, H; Prayoga, G; Azhar, A R; Azhar, R
Abstract: Sources of pollutants in the Cileungsi-Cikeas-Bekasi River Basin were inventoried, through data from the district's Environmental Agency where the three rivers cross. Pollutant sources were also determined based on searches in the form of type, number, and location, using google maps and google earth. The search results are mapped by applying ArcGIS. The aim of the research was to determine land-based source of pollution entering the river. The types and sources of pollutants vary greatly in terms of type, location, and number. In the three river basins, it is known that there were 413 industrial sectors, 538 restaurants, 457 housing complexes, 80 hospitals, 92 hotels, 53 shopping centers, 37 livestock, 147 small and medium sized entities (SMEs), and 59 domestic. The source of pollutants entering the Cikeas River was dominated by housing complexes. The source of pollutants entering the Cileungsi River was dominated by industry. Meanwhile, the sources of pollutants entering Bekasi River were mostly shopping centers, hotels, hospitals, and restaurants.